Peningkatan kinerja guru dalam pembelajaran melalui supervisi edukatif kolaboratif secara periodik di SDN 3 Palam Kota Banjarbaru - Kesuma Dewi (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2021)
A teacher must always improve his professional abilities, knowledge, attitudes and skills continuously according to the development of science and technology, including a new paradigm of education. The purpose of this study is to describe the steps for periodic collaborative educational supervision in implementing learning, assessing learning achievement, carrying out follow-up assessments of student learning achievement, compiling learning plans. This research is an action research, so this implementation is carried out in a cycle. The implementation is for two cycles. The cycles are a series that are mutually sustainable, meaning that the second cycle is a continuation of the first cycle. Every cycle there is always action preparation, action implementation, monitoring, evaluation, and reflection. 3. The periodic implementation of collaborative educational supervision can improve teacher performance in carrying out follow-up results of student achievement appraisals with the following steps. (1) The researcher and the teacher together make a follow-up program for the results of the assessment, (2) The researcher gives an example of the follow-up implementation, which is finally followed by the teacher in the actual implementation, (3) The researcher invites discussion to the teacher who has made, implemented, and analyzing follow-up programs. The conclusion of this study is that the improvement of teacher performance both in the lesson plans, the implementation of learning, the assessment of learning outcomes, and the implementation of follow-up on the results of student assessments in fact affect the results of student exams.